Parents' role in early sex education introduction for childhood in Taman Pintar Daycare Banda Aceh - Munawwarah, Munawwarah; Fajriah, Heliati; Misriaton, Misriaton (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2023)
Early sex education is an important thing to give to the individual since their childhood as the preventive action of doing immoral behavior that happening nowadays. Giving sex education for children is the responsibility of all parties, such as parents, teachers, societies, and government. This study aims at constructing the role of parents in introducing early sex education for early childhood and to find out the supporting and inhibiting factors of parents in introducing early sex education in Taman Pintar day care Banda Aceh, Indonesia. By using a qualitative descriptive method, the study collected the data through in-depth interview and documentation. The informants are parents who have children aged 4-5 years with total of 8 people. Data analysis used in this study is reduce data, data collection, data presentation and conclusions drawing. The results of this study indicate that the role of parents in introducing early sex education in children aged 4-5 years is very important. They are the closest people to the children, so that parents can be the first source of information for children and can be a model for their children. The supporting factors are parental education, modelling healthy behavior and , media content. While the inhibiting factors are fear of premature knowledge and lack of parental education.